Protocol for quantitative nuclear magnetic resonance for deciphering electrolyte decomposition reactions in anode-free batteries - Ming-Yue Zhou; Xiao-Qing Ding; Li-Peng Hou; Jin Xie; Bo-Quan Li; Jia-Qi Huang; Xue-Qiang Zhang; Qiang Zhang (STAR Protocols, 2022)
Summary: In this protocol, we describe the quantification of electrolytes using nuclear magnetic resonance. We detail the steps involved for battery cycling, sample preparation, instrument operation, and data analysis. The protocol can be used to quantify electrolyte decomposition reactions and the apparent electron transfer numbers of different electrolyte components. The protocol is optimized for lithium-based anode-free batteries but can also be applied to other rechargeable batteries.For complete details on the use and execution of this protocol, please refer to Zhou et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.